Analisis Pengaruh Sektor Pertanian Terhadap Pertumbuhan Ekonomi di Kabupaten Pasuruan dalam Perspektif Ekonomi Syariah tahun 2018 - 2023 - Naswa Aulia Syabilla; Nur Rahmatun Nazilah; Rohma Ningsih; Alimatul Farida (Economic Reviews Journal, 2025)
This study aims to analyze the impact of the agricultural sector, rice production, and harvested area on economic growth in Pasuruan Regency during the period from 2018 to 2023. Using secondary data from the Central Bureau of Statistics (BPS) and applying multiple linear regression analysis, this study evaluates the relationship between these variables and the Gross Regional Domestic Product (GRDP) of the agricultural sector. The analysis results show that the p-value for the three independent variables—agricultural sector, rice production, and harvested area—is 0.413, 0.572, and 0.256, respectively. These values are greater than 0.05, indicating that there is no significant effect of the agricultural sector on economic growth in Pasuruan Regency. These findings suggest that, although the agricultural sector plays an important role, economic growth in this area is more influenced by other sectors, such as manufacturing, trade, and mining. The study also highlights that the manufacturing sector is the dominant contributor, accounting for 60.42 percent of Pasuruan Regency's GRDP in 2023. This suggests that to achieve sustainable economic growth, management of the agricultural sector needs improvement to contribute more significantly to the local economy. The implications of this study provide insights for policymakers and stakeholders to formulate a more integrated development strategy, with a focus on strengthening the industrial sector and increasing agricultural productivity. In this way, it is hoped that more equitable welfare can be created for the people of Pasuruan Regency.